2019
DOI: 10.1177/1540415319856329
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Variability in Interpretation Modality Among Spanish-Speaking Patients With Limited English Proficiency

Abstract: Introduction: Provider–patient language discrepancies can lead to misunderstandings about follow-up care instructions and decreased adherence to treatment that may contribute to disparities in health outcomes among patients with limited English proficiency (LEP). This observational study aimed to understand how emergency department (ED) staff went about treating patients with LEP and examine the impact of consistent interpretation modality on overall patient satisfaction and comprehension. Method: A cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Finally, professional interpretation should be used for all aspects of patient care including disposition conversations. 25,30,54 Communication through interpreters appears to result in interactions that are less open-ended, and contains fewer topics or questions introduced by patients. 21 Whether or not communication and trust would be improved by specific awareness or skill training for use of interpreters remains uninvestigated.…”
Section: Use Of Interpretationmentioning
confidence: 99%
“…Finally, professional interpretation should be used for all aspects of patient care including disposition conversations. 25,30,54 Communication through interpreters appears to result in interactions that are less open-ended, and contains fewer topics or questions introduced by patients. 21 Whether or not communication and trust would be improved by specific awareness or skill training for use of interpreters remains uninvestigated.…”
Section: Use Of Interpretationmentioning
confidence: 99%
“…However, patients with LEP are less likely to use video telemedicine during the pandemic, 37 similar to prepandemic telemedicine findings 38 . Video interpretation has been demonstrated to be better than audio for retention of clinical information, 39 improved comprehension for consent, 40 and higher patient satisfaction 41 . However, a recent narrative review found no consensus about the most effective interpretation mode 27 .…”
Section: Discussionmentioning
confidence: 99%
“…38 Video interpretation has been demonstrated to be better than audio for retention of clinical information, 39 improved comprehension for consent, 40 and higher patient satisfaction. 41 However, a recent narrative review found no consensus about the most effective interpretation mode. 27 The interpreters in our • "It is good to ask.…”
Section: Contextmentioning
confidence: 99%
“…Most recent research among patients with LEP has specifically focused on addressing barriers in the treatment and management of pediatric ED cases (Choe et al, 2019;Gutman et al, 2018;Hartford et al, 2019;Malavé et al, 2019;Marshall et al, 2019;Portillo et al, 2021;Steinberg et al, 2016). Among recent interpretation studies in adult patient populations with LEP, a majority have primarily focused on understanding the influence of different modalities on satisfaction, comprehension, discharge preparedness, and repeated use of ED services (Balakrishnan et al, 2017;Lee et al, 2018;Schulson et al, 2018;Villalona et al, 2020).…”
mentioning
confidence: 99%